Monetary Uncertainty and Demand for Money Stability in Nigeria: An Autoregressive Distributed Lag Approach - El-Rasheed, Shehu; Abdullah, Hussin; Dahalan, Jauhari (EconJournals, 2017)
This paper investigates the effect of monetary uncertainty (MUC) on the stability of money demand function in Nigeria using the Autoregressive Distributed Lag approach for the period of 1980-2014. The demand for money in Nigeria is specified as a function of income, domestic interest rate, inflation, nominal exchange rate and MUC. The effect of MUC on money demand function has not been previously studied in the demand for money literature in Nigeria. The results from the bound testing indicate that MUC, income, domestic interest rate, inflation, exchange rate and broad money (M2) are co-integrated. The finding shows that MUC has a significant influence on the demand for money function in Nigeria. Evidence has shown a unidirectional causality running from MUC to money demand without feedback. The CUSSUM and CUSSUMSQ stability test established that the broad money demand function in Nigeria is stable over the period under study. By implication the monetary policies aimed at monetary targeting could be very effective even when there is the presence of significant MUC.